Taphonomy of the teleost Tselfatia formosa Arambourg, 1943 from Vallecillo, NE Mexico - Stinnesbeck, Eva Susanne; Herder, Fabian; Rust, Jes; Stinnesbeck, Wolfgang (PLOS ONE, 2023)
The platy limestone deposit of Vallecillo in northeastern Mexico is dated to the early-middle Turonian (Late Cretaceous) and known to contain a variety of well-preserved vertebrate fossils. One of the most common fish species is the teleost Tselfatia formosa. A review of 149 individuals reveals the presence of two types of body shapes (diamond-shaped and torpedo-shaped individuals) which is interpreted as sexual shape dimorphism (SSD). A unimodal size distribution illustrates a dominance of diamond-shaped specimens, but both body shape types are present in small (young) and big sized (old) individuals. The abundance of well-articulated and complete specimens suggests that T. formosa populated deep levels of the water column, which excluded buoyancy and flotation as well as carcass disintegration near the surface. The reconstruction of the dorsal and anal fins suggests the presence of a membrane between each fin ray and allows for ecological comparison of T. formosa with modern fan fishes.
Gesehen am 26.05.203